3分之1X+0.6X=28
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 20:21:54
3分之1X+0.6X=283分之1X+0.6X=283分之1X+0.6X=28x/3+0.6x=28x/3+3x/5=285x+9x=28×1514x=28×15x=30x/3+0.6x=28x/3+
3分之1X+0.6X=28
3分之1X+0.6X=28
3分之1X+0.6X=28
x/3+0.6x=28
x/3+3x/5=28
5x+9x=28×15
14x=28×15
x=30
x/3+0.6x=28
x/3+3x/5=28
5x/15+9x/15=28
14x/15=28
x/15=2
x=30
x+3分之1x=28
3分之1X+0.6X=28
0.3分之3x-1=0.6分之4-x +0.2分之3x+5
解方程;3分之x+x-1分之6=x(x-1)分之x+5
x²+x分之2+x²-x分之3=x平方-1分之4
X-3分之1=2+ 3-X分之X
x-1分之x-1=x+2分之3
6分之x-2=x分之x+3-1
4分之x+3=x-5分之x-1
4分之x+3=x-5分之x-1
3分之X+4分之X=3分之28
(x+2)分之(x+1)-(x+7)分之1=(x+3)分之(x+2)-(x+6)分之1
x-2分之x-(x-2)(x-3)分之1-x的平方=x-3分之2x
(x+2分之3x-x+2分之x)/x平方-4分之x(x-1)=4
X-6分之1X=8分之54分之1X+8分之3X=356分之5×5分之2+X=12分之7X-0.6X+5=7.8
解方程:x+3分之1x=28和x-3分之2x=4分之3快
【化简求值】(x分之x+2 - x-2分之x-1)÷x分之x-4【化简求值】(x分之x+2 - x-2分之x-1)÷x分之x-4x=3
x(x+1)分之1+(x+1)(x+2)分之1+(x+2)(x+3)分之1+.+(x+2010)(x+2011)分之1 x=1